Analisis Pendekatan Yesus dalam Resolusi Konflik Perebutan Kekuasaan di Kalangan Murid Berdasarkan Markus 10:35–45 - MANASE GULO (STT Gamaliel, 2026)
This study aims to offer Jesus’ approach to conflict resolution over the struggle for positions of power based on a biblical study. Power struggles continue to occur not only within governmental institutions but also within churches and Christian foundations. The method used is qualitative research with an exegetical approach. The findings reveal that conflicts over positions of power are driven by differences in interests, motivations, orientations, and goals. Based on biblical studies, four patterns of approach to resolving such conflicts were identified. First, the dialogical approach is used to facilitate questions and answers, discussions, and to bring conflicting parties together. Second, the parabolic communication approach is used to defuse the emotions of those in conflict, as the principle of parabolic communication avoids direct rebukes, emphasizes gentleness, and fosters peace. Third, the transformational approach seeks to change the paradigm of those in conflict regarding the concept of position and power from a worldly perspective to a spiritual one. Fourth, the paternal approach emphasizes love, acceptance, and is characterized by wise and nurturing words.